INTERFERENSI BAHASA MELAYU SAMBAS KE DALAM BAHASA INDONESIA PADA TUTURAN SISWA MTS YASTI SEKUDUK - Yuniarsih Yuniarsih; Hotma Simanjuntak; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe research is focused on The Sambas Malay Interference into Indonesian on the speech of Mts Yasti Sekuduk students. The problem in this study was regarding the types of language interference, forms of language interference, language interference factors and supplementation of learning texts in the Sambas Malay language interference into Indonesian on the speech of Yts Sekasti students.The method used was descriptive with a form of qualitative research. The data source was the informant and the data was in the form of a terminology regarding the Sambas Malay Interference into Indonesian on the speech of Mts Yasti Sekuduk students. The technique used was an interview while the data collection tool was in the form of a recording device and a camera from a cell phone, pens and notebooks. Based on the results of the analysis found that 49 language interference data, 9 data are in the form of language interference and 40 are language interference data in the form of language interference. Keywords: Keywords: Language Interference, Sambas Malay Language, Mts Yasti Sekuduk